2019
DOI: 10.2147/ijwh.s188938
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Chlamydia&nbsp;trachomatis</em> infection in primary fallopian tube and high-grade serous ovarian cancers: a pilot study</p>

Abstract: BackgroundThe aim of this study was to evaluate the association of Chlamydia trachomatis (CT) infection with primary tubal and high-grade serous ovarian cancers.MethodsThis is a cross-sectional, retrospective study conducted at Ain Shams University Maternity Hospital, Egypt, from February 2008 to October 2017. Sixty-seven paraffin archival blocks specimens were retrieved from cases who underwent staging laparotomy due to high-grade serous ovarian cancer (30 cases), primary tubal serous cancer (25 cases), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Chlamydia trachomatis was detected in 80% of EOC cases, which is consistent with prior research [26,31,56]. In fact, researchers have found C. trachomatis in 84% of high-grade fallopian tube serous cancers and in 17% of HGSOCs [57]. This evidence corroborates the negative impact of chlamydial infection on fallopian tube health particularly as HGSOC, the most lethal EOC histotype, originates within the fallopian tube [38].…”
Section: Discussionsupporting
confidence: 88%
“…Chlamydia trachomatis was detected in 80% of EOC cases, which is consistent with prior research [26,31,56]. In fact, researchers have found C. trachomatis in 84% of high-grade fallopian tube serous cancers and in 17% of HGSOCs [57]. This evidence corroborates the negative impact of chlamydial infection on fallopian tube health particularly as HGSOC, the most lethal EOC histotype, originates within the fallopian tube [38].…”
Section: Discussionsupporting
confidence: 88%
“…Based on the abovementioned, C. trachomatis has been implicated in ovarian cancer development [[16], [17], [18]]. Antibodies to C. trachomatis and chsp60 is associated with pelvic inflammatory disease (PID) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that C . trachomatis DNA is highly expressed in tubal serous cancer compared with high-grade serous ovarian cancer 26 . Some reports confirmed the presence of human papilloma virus (HPV) in malignant ovarian cancer 25,2734 , while others did not 3538 .…”
Section: Introductionmentioning
confidence: 99%